Epigenetic therapy: use of agents targeting deacetylation and methylation in cancer management - Ho, Allen S (Dove Medical Press, 2013)
The emergence of epigenetic mechanisms as key regulators of gene expression has led to dramatic advances in understanding cancer biology. Driven by complex layers that include aberrant DNA methylation and histone modification, epigenetic aberrations have emerged as critical processes that disrupt cellular machinery and homeostasis. Recent discoveries have already translated into successful clinical trials and improved patient care, with several agents approved for hematologic disease and others undergoing study. As the field matures, substantial challenges persist that will require resolution. These include the need to decipher more fully the interplay between the epigenetic and genetic machinery, patient selection and improving treatment efficacy in solid tumors, and optimizing combination therapies to counteract chemoresistance and minimize adverse effects. Here, we review recent progress in epigenetic treatments and consider their implications for future cancer therapy.